Redressing Institutional Abuse of Children - Daly, K. author. aut Link
XIII, 304 p.
Keywords: Winner of the Christine M. Alder Book Prize in 2015 from the Australian and New Zealand Society of Criminology Historical abuse of children is a worldwide phenomenon. This book assesses the enablers of abuse and the reasons it took so long for officials to respond. It analyzes redress for institutional abuse in two countries, Canada and Australia, using first-hand accounts of survivors' experiences. .